The satellite derived surface radiation budget for BALTEX - Hollmann, R.; Gratzki, A. (Boreal Environment Research Publishing Board, 2024)
The Satellite Application Facility for Climate Monitoring (CM-SAF) will derive operationally consistent cloud and radiation parameters in high spatial resolution for an area that covers Europe and part of the north Atlantic Ocean in an off-line mode. The availability of the 12-channel instrument SEVIRI and the GERB onboard the MSG satellite, together with the five-channel AVHRR instrument onboard the NOAA and METOP satellites provides a unique opportunity to derive consistent cloud and radiation parameters. The cloud and surface radiation products will be based on data from the polar orbiting satellites NOAA and METOP for the northern latitudes, and on data from the MSG satellite for the mid-latitudes. To reduce inhomogeneities in the transition from the mid-latitudes to the northern latitudes as much as possible, the same algorithms will be used for both areas. Here a brief description of the planned surface radiation budget products and the selected algorithms is given.